(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Lillian Hellman was impressed and influenced by writings of Ibsen, Brecht, Strindberg and Chekhov, and she also shows considerable influence of native writers too, like Eugene O’Neill and Dashiell Hammett. Eugene O’Neill was a senior contemporary playwright of Lillian Hellman, and much before her appearance on the American stage, O’Neill had already carved a niche for himself as a formidable playwright. He introduced psychological realism in his plays, so do we notice this element in Hellman’s plays as well. Freudian overtones gave American plays a new vitality and originality. In fact, the psychoanalytical theories of Freud had moved and influenced almost all the writers of the 1930s, and even the subsequent ones. Their plays are full of aberrant and inverted relationships - incestuously lustful fathers, mothers, brothers and sisters, adulterous men and women, homosexual love relationships and repressed sexual instincts, to name just a few psychological issues. Both O’Neill and Hellman sought to portray how the hidden psychological processes affect the outward actions of their characters. In Mourning Becomes Electra (1931), O’Neill uses a Greek legend as his model, and Hellman’s Hubbard plays also exhibit considerable resemblance to Aeschylus’s trilogy, the Oresteia. However, Hellman’s strong protest against the passive indifference of the bystanders in the face of social and moral evils takes her plays beyond the realm of pure tragedy, unlike O’Neill’s, who adheres to the Greek pattern to a sizeable degree. Like O’Neill, Hellman’s good characters too wrestle with societal constrictions, and usually give in to forces they are powerless to control. O’Neill in Long Day’s Journey into Night (1935) which is an autobiographical play showed agonized relationships between members of a family (father, mother and two sons), and Hellman’s no play is free from such painful relationships.